Pengaruh Coping Strategies terhadap Psychological Distress pada Kelompok Remaja akhir Pasca Putus Cinta - Putri Adelia Anjani; Netty Merdiaty; Sulistiasih S (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the effect of coping strategies on psychological distress in late adolescents after a breakup. Breakups are one of the events that can cause psychological distress in late adolescents. This condition can trigger various emotional responses such as stress, anxiety, and depression, which are reflected in psychological distress. One factor suspected of playing a role in this condition is coping strategies, which are efforts made by individuals to face and manage the stress experienced. This study used a quantitative approach with a descriptive research type. The sampling technique used was non-probability sampling with a purposive sampling method. The study subjects were 100 women aged 18–21 years who resided in Bekasi City and had experienced a breakup in the past six months. Data collection was conducted using the Brief COPE scale to measure coping strategies and the DASS-21 scale to measure psychological distress. The results showed that coping strategies had a significant effect on psychological distress. Furthermore, a coefficient of determination (R²) of 0.132 was obtained, indicating that coping strategies contributed 13.2% to psychological distress, while the remaining 86.8% was influenced by factors outside the study. Therefore, the hypothesis that coping strategies influence psychological distress in late adolescent girls after a breakup is accepted.